2019
DOI: 10.2113/jeeg24.4.653
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Applications of the Helicopter-borne Transient Electromagnetic System CAS-HTEM

Abstract: Over the past decade, helicopter-borne transient electromagnetic (HTEM) systems have been rapidly developed. A new HTEM prototype (referred to as a CAS-HTEM) has been developed by the Chinese Academy of Sciences. In terms of hardware, the CAS-HTEM system uses an inflatable structure to carry the transmitting loop, which significantly reduces the weight of the system and makes it easier to transport. A dual gain receiver was innovated to extend the dynamic range of the system. In addition, an observation circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Optical remote sensing data preprocessing mainly includes geometric correction, radiation correction, and mosaic, of which geometric correction uses the corrected 1:50,000 topographic map as a reference, and the RMS error falls within a pixel. Atmospheric radiation correction was completed in the FLASSH atmospheric correction module of the ENVI4.8 software to form the reflectivity image, and then the image was enhanced and cut [35][36][37][38]. Non-remote sensing information sources mainly include geological environment background data, topographic maps (1:50,000), geological maps, administrative division maps, and water system maps.…”
Section: Data Source and Preprocessingmentioning
confidence: 99%
“…Optical remote sensing data preprocessing mainly includes geometric correction, radiation correction, and mosaic, of which geometric correction uses the corrected 1:50,000 topographic map as a reference, and the RMS error falls within a pixel. Atmospheric radiation correction was completed in the FLASSH atmospheric correction module of the ENVI4.8 software to form the reflectivity image, and then the image was enhanced and cut [35][36][37][38]. Non-remote sensing information sources mainly include geological environment background data, topographic maps (1:50,000), geological maps, administrative division maps, and water system maps.…”
Section: Data Source and Preprocessingmentioning
confidence: 99%
“…At present, China has carried out large-scale application of airborne electromagnetic exploration technology, mainly in uranium and polymetallic mineral exploration. Airborne electromagnetic method can measure the signal of artificial or natural field source passing through the underground geological body to study the distribution of the geological body in the underground space [3,4]. The effective experimental application in railway engineering exploration in complex terrain areas in China has further expanded the application scenarios of airborne electromagnetic method.…”
Section: Forewordmentioning
confidence: 99%
“…The Geotech VTEM system, earlier focusing on late-gate data quality for deep mineral exploration, has indicated that placing the receiver in the center of the transmitting coils shielded by a concentric bucking coil could effectively improve the near-surface imaging [ 10 ]. Some other HTEM systems with similar configuration include the Xcite system by New Resolution Geophysics [ 11 ], the CAS-HTEM by the Chinese Academy of Sciences [ 12 ], and so on. Moreover, the AeroTEM-IV system manufactured by Aeroquest (acquired by Geotech) is the first to introduce the eccentric bucking coil into the HTEM system [ 13 ].…”
Section: Introductionmentioning
confidence: 99%